A Historical Review of Trademark - Bhardwaj, Dr Manish (Innovative Research Thoughts, 2017)
Brands' trademarks are the most solid, well-documented, and measurable element of this issue. This editorial presents an overview of the seven pieces contained in this issue, summarises prior contributions from economic, legal, commercial, and historical literature, and speculates on future study. Patents and copyright have long trumped trademarks as the most valuable intellectual property. Since 1987, there have been few new theoretical advancements, and those that have largely remained within the framework of the previous generation.